Early morning salivary cortisol is not associated with extraversion - Munafo, MR; Lee, L; Ayres, R; Flint, J; Goodwin, G; Harmer, C (2006)
An association between salivary cortisol levels and neuroticism has recently been reported, but it is unclear whether this association is unique to neuroticism or extends to other personality measures. The present study investigated early morning salivary cortisol levels in individuals selected for high and low extraversion. Thirty-three healthy volunteers were selected on the basis of their score on the extraversion sub-scale of the Eysenck Personality Questionnaire, and provided fasting saliva samples upon waking and at 15-min intervals for the next hour. Repeated measures ANOVA indicated a main effect of time (p < 0.001). The main effect of group (p = 0.196) and the group × time interaction (p = 0.588) were on-significant. Our data support the dissociation of the neurobiological correlates of behavioral traits. Unlike in the case of neuroticism, extraversion appears not to be associated with variability in early morning salivary cortisol level. © 2005 Elsevier Ltd. All rights reserved.